1995
DOI: 10.1038/ki.1995.324
|View full text |Cite
|
Sign up to set email alerts
|

Renal proximal tubular epithelium from patients with nephropathic cystinosis: Immortalized cell lines as in vitro model systems

Abstract: The renal proximal tubule is a major site of injury in a variety of congenital/metabolic diseases including nephropathic cystinosis, the most commonly known cause of renal Fanconi's syndrome. In this lysosomal storage disease there are defects in proximal tubule function within the first few months of life. While culture of renal tubular cells from the urine of these patients is possible, development of immortalized cell lines would insure large numbers of homogeneous cells for studies of renal epithelial cell… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
43
0

Year Published

2000
2000
2019
2019

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 58 publications
(43 citation statements)
references
References 33 publications
0
43
0
Order By: Relevance
“…In situ hybridization using the digoxigenin-substituted 220-bp PRKX PCR fragment as probe (Figure 2A through D) showed that PRKX mRNA transcripts were specifically local- ized throughout the ureteric bud epithelial cells of 14-to 17-wk human fetal kidneys from the medullary truncal regions through to the cortical branching tips, which also expressed the characteristic ureteric bud epithelial markers cytokeratin ( Figure 2E) and polycystin-1 ( Figure 2F) (24,25). PRKX mRNA and protein are also highly expressed in primary and differentiated conditionally immortalized human renal HFCT epithelial cell lines derived from microdissected fetal kidneys (Figure 3, A and B).…”
Section: Prkx Is Expressed Throughout the Fetal Kidney Ureteric Bud Tmentioning
confidence: 99%
See 1 more Smart Citation
“…In situ hybridization using the digoxigenin-substituted 220-bp PRKX PCR fragment as probe (Figure 2A through D) showed that PRKX mRNA transcripts were specifically local- ized throughout the ureteric bud epithelial cells of 14-to 17-wk human fetal kidneys from the medullary truncal regions through to the cortical branching tips, which also expressed the characteristic ureteric bud epithelial markers cytokeratin ( Figure 2E) and polycystin-1 ( Figure 2F) (24,25). PRKX mRNA and protein are also highly expressed in primary and differentiated conditionally immortalized human renal HFCT epithelial cell lines derived from microdissected fetal kidneys (Figure 3, A and B).…”
Section: Prkx Is Expressed Throughout the Fetal Kidney Ureteric Bud Tmentioning
confidence: 99%
“…Briefly, microdissected human fetal (19 wk) collecting tubules (HFCT) were conditionally immortalized using a temperature-sensitive T antigen expressing retroviral vector (25) and clonal cells lines derived by limiting dilution. For studies described here, the HFCT clone 7F was grown to 70% confluence at 33°C then transferred to the nonpermissive temperature of 37°C for 7 to 10 d before use in adhesion and migration assays.…”
Section: Cell Culturementioning
confidence: 99%
“…To conditionally immortalize proximal tubular epithelial cells (PTEC), we developed a lentiviral vector encoding the tsTag allele tsA58U19 (20). tsTag was subcloned into pIRES-hyg (Clontech, Palo Alto, CA).…”
Section: Viral Transductionmentioning
confidence: 99%
“…A normal human kidney epithelial cell line (NHK52) bearing a temperature-sensitive SV40 large T-antigen plasmid was provided by Dr. L.C. Racusen (Racusen et al 1995). NHK cells were maintained in media containing 50% Ham's F12, 50% Dulbecco's modified Eagles' medium, 5% fetal bovine serum, 25 mM Hepes, 2.5 g/ml insulin, 50 ng/ml hydrocortisone, 5 g/ml transferrin, 5 ng/ml sodium selenite, 20 ng/ml triiodothyronine, 50 U/ml penicillin, 50 g/ml streptomycin, and 2.5 g/ml amphotericin.…”
Section: Cell Culturementioning
confidence: 99%